2016
DOI: 10.18865/ed.26.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Race Differences in the Relationship between Obesity and C-Reactive Protein

Abstract: <p>C-reactive protein (CRP) is a risk factor for cardiovascular disease and mortality; it is known to be positively associated with obesity but there is some evidence that this association differs by race or sex. We used nationally representative data of adults aged &gt;50 years to investigate sex and race modifiers of the associations between obesity and CRP in non-Hispanic White males (n=3,517) and females (n=4,658), and non-Hispanic Black males (n=464) and females (n=826). Using multiple linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Consistent with our studies, many studies have addressed sex differences in the independent correlations between leptin and CRP and these associations were only seen in women [32] or were stronger in women than men [33-36]. Abdullah et al [32] reported strong independent correlations between leptin and CRP in women.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our studies, many studies have addressed sex differences in the independent correlations between leptin and CRP and these associations were only seen in women [32] or were stronger in women than men [33-36]. Abdullah et al [32] reported strong independent correlations between leptin and CRP in women.…”
Section: Discussionsupporting
confidence: 90%
“…Our conceptual and methodologic framework permitted us to isolate the role of maternal obesity from all other pathways through which the racial disparity in poor perinatal outcomes may operate. We accomplished this via inverse probability weighting, which simultaneously adjusted for potential confounding of the association between prepregnancy obesity and adverse perinatal outcomes, while quantifying the total racial disparity in these same outcomes . We specifically chose not to adjust for additional racially disparate comorbidities (e.g., gestational hypertension), which may also account for a portion of the racial disparity in infant mortality, as this would have led to an overestimation of obesity's role in explaining the disparity .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, at 10%, the prevalence of severe obesity (BMI ≥35 kg/m 2 ) in non‐Hispanic Black women is twice the rate of their non‐Hispanic White counterparts . Finally, a growing body of research has suggested important biological differences in obesity phenotypes and the effect of obesity across racial groups, including adipose tissue deposition and associations with C‐reactive protein .…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in the relationship between BMI and health risk is recognized (Clark et al, 2016). Men have been shown to develop diabetes at a younger age compared to women (Logue et al, 2011;Kautzky-Willer et al, 2016).…”
Section: Bmi Cut-off For Identifying Cvd Risk Factorsmentioning
confidence: 99%
“…Due to observations that the World Health Organization (WHO) recommended, BMI cut-off underestimate obesity in certain populations, further studies in different ethnic groups were also suggested (Clark et al, 2016). In response to Asian studies, the WHO recommended lower BMI cut-off for Asia-Pacific region (WHO, 2000a).…”
Section: Introductionmentioning
confidence: 99%